2008
DOI: 10.1073/pnas.0708615105
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive nitric oxide synthase activation is a significant route for nitroglycerin-mediated vasodilation

Abstract: The physiological effects of nitroglycerin as a potent vasodilator have long been documented. However, the molecular mechanisms by which nitroglycerin exerts its biological functions are still a matter of intense debate. Enzymatic pathways converting nitroglycerin to vasoactive compounds have been identified, but none of them seems to fully account for the reported clinical observations. Here, we demonstrate that nitroglycerin triggers constitutive nitric oxide synthase (NOS) activation, which is a major sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
34
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 37 publications
(47 reference statements)
7
34
4
1
Order By: Relevance
“…In fact, many articles have shown that endogenously produced NO antagonizes the effect of nitroglycerin. As an example, mechanical removal of the endothelium, which rids the vessel of NO production, has repeatedly been shown to enhance nitroglycerin vasodilatation, in contrast to the finding by Bonini et al (1). Inhibition of NOS with agents such as L-NAME has also been shown to enhance nitroglycerin-induced vasodilatation, again contradicting the findings of Bonini et al (1).…”
contrasting
confidence: 55%
See 2 more Smart Citations
“…In fact, many articles have shown that endogenously produced NO antagonizes the effect of nitroglycerin. As an example, mechanical removal of the endothelium, which rids the vessel of NO production, has repeatedly been shown to enhance nitroglycerin vasodilatation, in contrast to the finding by Bonini et al (1). Inhibition of NOS with agents such as L-NAME has also been shown to enhance nitroglycerin-induced vasodilatation, again contradicting the findings of Bonini et al (1).…”
contrasting
confidence: 55%
“…As an example, mechanical removal of the endothelium, which rids the vessel of NO production, has repeatedly been shown to enhance nitroglycerin vasodilatation, in contrast to the finding by Bonini et al (1). Inhibition of NOS with agents such as L-NAME has also been shown to enhance nitroglycerin-induced vasodilatation, again contradicting the findings of Bonini et al (1). Finally, mice lacking the endothelial isoform of NOS exhibit augmented vasodilatation to nitroglycerin (2, 3), and overexpression of this enzyme in transgenic mice paradoxically reduces nitroglycerin-and sodium nitroprusside-induced vasodilatation (4).…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…This means that a large fraction of the NO derived from the glyceryl trinitrate patches is diverted to react and be scavenged by cell-free hemoglobin instead of playing its expected effect on blood vessels. Third, it has been shown that the vasodilatory action of low-dose glyceryl trinitrate is partly due to NOS-dependent mechanisms (65). NOS (both eNOS and nNOS isoforms) are dysfunctional in mice with ECM (37); therefore, it is conceivable that the action of glyceryl trinitrate through this mechanism is impaired in mice with ECM, also explaining the need for higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent PNAS article (1) we demonstrated that endothelial NOS (eNOS) is phosphorylated at Ser-1177, an index of eNOS activation, in HUVEC and blood vessels of rodents challenged with nitroglycerin. In addition, we showed that the time scale in which this phosphorylation happens correlates with the drop in the blood pressure.…”
mentioning
confidence: 99%